Service quality on customers’ satisfaction and loyalty. Survey evidence on mediation role of trust in Islamic banks - Haron, Razali; Abdul Subar, Noradilah; Ibrahim, Khairunisah (2019)
The objective of this study is to examine the impact of PAKSERV measures on customers’ satisfaction, loyalty and trust in Malaysian Islamic banks. These comprehensive measures concern on the cultural dimension of service quality by focusing on the mediating role of trust in the Malaysian context. A survey was conducted involving 401 Islamic bank customers in the states of Kuala Lumpur and Selangor, Malaysia. The data were analysed through exploratory factor analysis, confirmatory factor analysis and structural equation modeling employing AMOS 23 and SPSS 23. The study found positive relationship of PAKSERV dimensions of service quality, customer satisfaction, customer loyalty, and the mediating role of trust in enhancing customers’ loyalty. This study provides new evidence on how trust can act as a partial mediation on the relationship between customer satisfaction and customer loyalty in the cultural context of Malaysian Islamic banking sector. The findings of this study can be used as a framework for other Islamic financial institutions (IFIs) such as the Islamic social finance institutions in improving services to its customers.